Dynamic Medial Patellofemoral Ligament Reconstruction in Patellar Instability: A Surgical Technique - Anna Bartsch MD; Sebastian Müller MD; Christian Egloff MD (SAGE Publishing, 2021)
Background: Patella instability with recurrent dislocations is a result of various pathologies, for example, patella alta, trochlea dysplasia or medial patellofemoral ligament (MPFL) rupture. The recurrent dislocation rate of conservatively treated chronic patellar instability is high; therefore, it is recommended to manage it surgically. This video presents a new operative approach to stabilize the patella in a dynamic MPFL reconstruction, which addresses the most common complications occurring in static reconstructions: malpositioning and overtensioning the graft. Indications: Surgical indications for the new dynamic procedure mirror the indications for static MPFL reconstruction. This is MPFL insufficiency (patella instability in the first 30° of knee flexion), which is most frequently seen in recurrent lateral patella dislocations. Moreover in very rare cases of first patella dislocation with a patellar instability severity score equal or higher than 4. Technique Description: The dynamic MPFL reconstruction consists of 3 steps: First, detaching and mobilizing the gracilis muscle at its anatomical insertion. Second, redirecting the freed gracilis muscle to its new patellar insertion. Third, reinserting the gracilis muscle at the patella. Results: The dynamic MPFL reconstruction has the advantage of lesser risk of overtensioning and malpositioning the graft. The insertion point of the MPFL surrogate is easier to locate, and the patella is dynamically stabilized through reflectory gracilis muscle contraction. Compared with the static reconstruction, only one instead of 3 holes have to be drilled and only 1 interference screw has to be placed, thus shortening the surgery time. From a theoretical biomechanical perspective, the dynamic tensioning is superior to the static procedure. The few accomplished studies published so far by Becher et al and Ostermeier et al show good or better functional results (Kujala, Lysholm, Tegner scores) with the dynamic MPFL reconstruction, yet higher evidence studies need to be performed. Conclusion: Dynamic MPFL reconstruction appears to be a simpler and more effective surgical technique for MPFL reconstruction. Because of its novelty, high evidence studies assessing long-term therapeutical outcomes are still lacking and need to be conducted in order to compare it conclusively with the static procedure.